2023
DOI: 10.3389/fnagi.2023.1290657
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study in Alzheimer’s disease: a bibliometric and visualization analysis

Junyao Zhang,
Yinuo Wang,
Yingying Zhang
et al.

Abstract: BackgroundThousands of research studies concerning genome-wide association studies (GWAS) in Alzheimer’s disease (AD) have been published in the last decades. However, a comprehensive understanding of the current research status and future development trends of GWAS in AD have not been clearly shown. In this study, we tried to gain a systematic overview of GWAS in AD by bibliometric and visualization analysis.MethodsThe literature search terms are: (“genome-wide analysis” or “genome-wide association study” or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 93 publications
(112 reference statements)
0
1
0
Order By: Relevance
“… Fei et al (2022) found that “circular RNAs,” “regulation of neuroinflammation,” and “tau protein” were the future research directions of non-coding RNAs in AD. Other studies have indicated that tau protein is a keyword associated with glial fibrillary acidic protein (GFAP), mitochondrion, GWAS, and biomarkers in AD ( Noda et al, 2023 ; Song R. et al, 2023 ; Zhang J. et al, 2023 ; Zou et al, 2023 ). Neuroinflammation refers to the activation of immune responses within the CNS, specifically involving glial cells such as microglia and astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“… Fei et al (2022) found that “circular RNAs,” “regulation of neuroinflammation,” and “tau protein” were the future research directions of non-coding RNAs in AD. Other studies have indicated that tau protein is a keyword associated with glial fibrillary acidic protein (GFAP), mitochondrion, GWAS, and biomarkers in AD ( Noda et al, 2023 ; Song R. et al, 2023 ; Zhang J. et al, 2023 ; Zou et al, 2023 ). Neuroinflammation refers to the activation of immune responses within the CNS, specifically involving glial cells such as microglia and astrocytes.…”
Section: Discussionmentioning
confidence: 99%